KONSERVASI ALAM DAN KAITANNYA DENGAN BENCANA: STUDI TERHADAP TAFSIR AL-QUR’AN DALAM SURAH AL-A’RAF AYAT 56-58 - Muhammad Hafizh Ridho; Ardiansyah (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This study explores the correlation between environmental conservation and natural disasters through an interdisciplinary analysis of Surah Al-A’raf verses 56-58 and scientific data on environmental degradation. Employing a qualitative approach, the research delves into classical and contemporary Qur’anic interpretations, including Tafsir Ibnu Katsir and Tafsir Al-Mishbah, to elucidate the theological principles of stewardship (khalifah) and balance (mizan). Empirical data from authoritative sources such as the Intergovernmental Panel on Climate Change (IPCC) and the Food and Agriculture Organization (FAO) are incorporated to demonstrate how anthropogenic environmental damage—such as deforestation and pollution—is closely linked to the increasing frequency of natural disasters. Case studies from Indonesia, particularly reforestation programs spearheaded by Islamic organizations such as Nahdlatul Ulama, serve to illustrate the practical implementation of Islamic environmental ethics. The findings underscore that integrating Islamic teachings with scientific insights provides a comprehensive and holistic strategy for addressing ecological crises and mitigating disasters, emphasizing the pivotal role of conservation within both spiritual and scientific paradigms